2012
DOI: 10.1177/1470320312465220
|View full text |Cite
|
Sign up to set email alerts
|

Association of all-trans retinoic acid treatment with the renin-angiotensin aldosterone system expression in glomerulosclerosis rats

Abstract: Background and objective: All-trans retinoic acid (ATRA), a promising therapeutic agent, has been confirmed in animal experiments as playing a protective role against renal diseases. The renin-angiotensin aldosterone system (RAAS) plays a key role in the pathogenesis of renal diseases, and RAAS inhibitors can prevent the progression of kidney diseases. In our previous study, we found that ATRA could play a protective role against glomerulosclerosis (GS) lesions in rats, and its effect was similar to RAAS inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…These results are in concordance with our previous study, in which we found that ATRA treatment was associated with reduced expression of ACE1 and increased expression of ACE2 in glomerulosclerosis rats. 7 Furthermore, Zhong et al 23 reported that chronic ATRA treatment increased both gene and protein expression of ACE2, which resulted in the reduction of blood pressure and the attenuation of myocardial damage in spontaneously hypertensive rats. ATRA was associated with up-regulated expression of ACE2, and their results and conclusion were similar to ours, albeit in a different cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in concordance with our previous study, in which we found that ATRA treatment was associated with reduced expression of ACE1 and increased expression of ACE2 in glomerulosclerosis rats. 7 Furthermore, Zhong et al 23 reported that chronic ATRA treatment increased both gene and protein expression of ACE2, which resulted in the reduction of blood pressure and the attenuation of myocardial damage in spontaneously hypertensive rats. ATRA was associated with up-regulated expression of ACE2, and their results and conclusion were similar to ours, albeit in a different cell type.…”
Section: Discussionmentioning
confidence: 99%
“…1 ATRA has been implicated to play a significant role in a number of diseases, such as acute myeloid leukemia, hepatocellular carcinoma, glomerulosclerosis, renal interstitial fibrosis (RIF), etc., [2][3][4][5][6][7] either actively through changes in its levels or positively affecting some of the aforementioned disease via ATRA treatment. Histopathologically, RIF is characterized by distinct tubulointerstitial changes, including interstitial cell infiltration, tubular degeneration, increased number of myofibroblasts, oxidative stress, and accumulation of profibrotic factors and extracellular matrix (ECM) components.…”
Section: Introductionmentioning
confidence: 99%
“…The primary function of ALDH1A2 is to synthesize retinoic acid from vitamin A. Retinoic acid has been extensively studied in relation to kidney disease and has been considered a potential therapeutic agent because of its anti‐inflammatory, antifibrotic, and cell differentiation properties . In regard to BP regulation, retinoic acid administration has been shown to modify the expression of renin–angiotensin–aldosterone system components and leads to decreased BP in a rat model . Studies have also shown that the retinoic acid receptor RXR dimerizes with peroxisome‐proliferator‐activated receptor‐γ to upregulate renin gene expression .…”
Section: Discussionmentioning
confidence: 99%
“…There are in vivo and in vitro arguments in animals reporting the effects of RA on renin or angiotensin production ( 96 , 97 , 98 , 99 ). atRA treatment increased the expression of angiotensin-converting enzyme 2 with a subsequent reduction of blood pressure in hypertensive rats.…”
Section: Miscellaneousmentioning
confidence: 99%